To find the product of the polynomial expressions \((xy+1)(x-3)\), we can use the distributive property (also known as the FOIL method in this case).
-
Distributing \(xy\) to both terms in \((x-3)\):
- \(xy \cdot x = x^2y\)
- \(xy \cdot (-3) = -3xy\)
-
Distributing \(1\) to both terms in \((x-3)\):
- \(1 \cdot x = x\)
- \(1 \cdot (-3) = -3\)
Now we can combine all the products: \[ x^2y - 3xy + x - 3 \]
So, the correct product of the expressions \((xy+1)(x-3)\) is: \[ x^2y - 3xy + x - 3 \]
Thus, the answer is: x²y - 3xy + x - 3 (Response 1)